An Investigation on the Relationship between the Stability of Lithium Anode and Lithium Nitrate in Electrolyte. Issue 15 (22nd October 2019) - Yu, Linghui; Song, Jiajia; Wang, Luyuan Paul; Ong, Samuel Jun Hoong; Gu, Chengding; Liao, Hanbin; Wang, Ting; Chen, Wei; Lev, Ovadia; Xu, Zhichuan J.
Abstract : Understanding the relationship between lithium anode and electrolyte is important to develop a more compatible lithium/electrolyte system for stable and safe cycling of lithium-metal based batteries. However, to date, there has not been any work to quantify the effects of electrolyte on the performance of electrode due to the complexity. Herein, we quantify the relationship between an electrolyte additive, LiNO3, and the stability of lithium anode. It is found that, with increasing the amount of LiNO3, the cyclability of lithium anode rises linearly and the risk of dendrite-induced short circuits can be reduced. Low Coulombic efficiency (CE) and short circuits tend to occur in tandem. LiNO3 is found to be continuously consumed upon electrochemical cycling, which leads to a low CE and a high risk of short circuits.